(untitled) (Biological Sciences - PJSIR, 2016)
Polyethylene glycol (PEG-6000) is often used for the early establishment screening of the wheat genotypes against drought stress conditions. A collection of twenty-one newly developed bread wheat genotypes (developed through conventional and mutational breeding techniques) and four commercial drought tolerant check varieties were included in screening at seedling stage under three treatments of PEG-6000; T1 (0.5 MPa) and T2 (0.75 MPa) along with control T3 (distill water only). Three important early growth establishment traits like germination percentage, root length and shoot length of the wheat genotypes were observed. Significant variation among genotypic means regarding the observed traits was recorded at both the treatments. Wheat genotypes performance including check varieties for germination percentages was recorded as T1 (86.1%), T2 (72.4%) with reduction percentage of 12.5% and 33.8%. Root length of genotypes decreased by 37.0% in 0.5 MPa and 82.75% in 0.75 MPa, whereas, shoot length reduction was recorded as 38.9% (T1) and 84.6% (T2) as compared to control. This study provided essential information about the performance of advanced wheat genotypes under water stress conditions at early seedling establishment.